2021
DOI: 10.1016/j.heliyon.2021.e07581
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexation of the anticancer drug pomalidomide with cyclodextrins: fast dissolution and improved solubility

Abstract: Pomalidomide (POM), a potent anticancer thalidomide analogue was characterized in terms of cyclodextrin complexation to improve its aqueous solubility and maintain its anti-angiogenic activity. The most promising cyclodextrin derivatives were selected by phase-solubility studies. From the investigated nine cyclodextrins – differing in cavity size, nature of substituents, degree of substitution and charge – the highest solubility increase was observed with sulfobutylether-β-cyclodextrin (SBE-β-CD). The inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…On the contrary, total dissolution of POM as a coarse suspension (POM-CMCS) was reached only after 6 h. The dissolution rate of the raw drug was even slower than that of POM-CMCS, as after 8 h only 38% of raw POM dissolved into the buffer solution. This slow dissolution of POM, whether as the raw drug or as a coarse suspension, is in line with the recent studies of Szabó et al (Szabó et al 2021), who similarly demonstrated slow dissolution into both Britton-Robinson buffer at pH 7.0 and simulated gastric fluid at pH 1.6. The substantial increase in the the solubility of POM formulated as nanosuspension and its immediate dissolution clearly indicates that nanosizing may increase the POM absorption rate and, therefore, the bioavailability after i.p.…”
Section: Dissolution Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, total dissolution of POM as a coarse suspension (POM-CMCS) was reached only after 6 h. The dissolution rate of the raw drug was even slower than that of POM-CMCS, as after 8 h only 38% of raw POM dissolved into the buffer solution. This slow dissolution of POM, whether as the raw drug or as a coarse suspension, is in line with the recent studies of Szabó et al (Szabó et al 2021), who similarly demonstrated slow dissolution into both Britton-Robinson buffer at pH 7.0 and simulated gastric fluid at pH 1.6. The substantial increase in the the solubility of POM formulated as nanosuspension and its immediate dissolution clearly indicates that nanosizing may increase the POM absorption rate and, therefore, the bioavailability after i.p.…”
Section: Dissolution Studiessupporting
confidence: 91%
“…The POM endotherm is slightly shifted towards a lower temperature, possibly due to the drug's small particle size in the nanocrystalline suspension, dissolution of the drug in the stabilizer during the DSC run, or strong interaction between the drug and the stabilizer, as also suggested by the decreased enthalpy of POM in the formulation. (Szabó et al, 2021) the sharp diffraction peaks of bulk POM powder at 12.3, 14.1, 16.9, 17.3, 18.3, 24.3, 24.7, 25.6, and 28.0 2ϑ indicate its crystalline nature. Also in the POM-NS diffractogram the characteristic peaks of POM are clearly evident, thus suggesting that its crystal pattern is not affected by the formulation process.…”
Section: Dsc Analysesmentioning
confidence: 99%
“…No. P2074, logP = 0.01, pKa = 1.89 [ 20 ]) was provided by Tokyo Chemical Industry (Tokyo, Japan). HPLC-grade water (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclodextrins are cyclic oligosaccharides with a polar moiety and a hydrophilic external surface that are structurally linked. 15 The inclusion complexation approach has been employed for various drugs for improving their solubility and dissolution rate, like pomalidomide (), 16 docetaxel, 17 etodolac, 18 and econazole nitrate. 19…”
Section: Techniques For Solubility Improvementmentioning
confidence: 99%